Preparation of cathode material with LiMn2O4 using conductive carbon-sodium alginate as three dimensional collector system. (1st September 2021) - Li, Peizhi; Zhu, Jiaqi; Wang, Chen; Wang, Jiangtao; Yang, Xiaowu; Zhang, Kang; Shen, Zhifeng; Qiu, Guanjun; Han, Fei; Hou, Yan
Abstract: In this paper, sodium alginate and conductive carbon black were used as three-dimensional collector of lithium manganate electrode, which has the soft and flexible characteristics. The structure of the electrode was characterized by Raman and X-ray diffraction (XRD), and the micro morphology and elements of the electrode were analyzed by SEM and EDS. Its electrochemical performance was tested by constant current charge-discharge curve. The results show that the specific discharge capacity of the three-dimensional collector based on sodium alginate is 125.25 mAh g −1 in the first cycle at 100 mA g −1 current density, the capacity retention rate is 96.94% in the 100th cycle, and the capacity decay rate is 3.06%. After 200 cycles, the reversible specific discharge capacity is 120.50 mAh g −1, the capacity retention rate is 96.78%, and the capacity decay rate is only 3.22%. The specific capacity of the electrode is restored to 90.35% of the initial rate by charging and discharging tests at different rates, which indicates that the rate of electrode can perform better. SEM and EDS tests on the electrode after 200 cycles show that the electrode does not shed a large amount of lithium manganese ate after a long cycle, and the three-dimensional spongy structure of the fluid collector reduces the damage caused by the volume expansion of active substances, which is the main reason for its good cycling performance. Graphical abstract: Image, graphical abstract